Unraveling the spatial distribution of the acidity of HZSM‐5 zeolite on the level of crystal grains. Issue 4 (6th January 2021) - Xian, Xiaochao; Chen, Jun; Chu, Yirong; He, Mengjun; Zhao, Shuo; Dong, Lichun; Ren, Jingzheng
Abstract: Here we developed a new method to quantitatively characterize the spatial distribution of the Brønsted acidity of HZSM‐5 zeolite on the crystal grains level indirectly. The Brønsted acid sites of HZSM‐5 zeolite completely covered or blocked by previous coke deposition were released gradually from the outer surface to the center of the crystal grains via shrinking core mode isothermal oxidation with high temperature and low oxygen concentration. The spatial distribution of the coke was obtained based on the one‐dimensional position coordinate L rp through building and solving an enhanced shrinking core model. Then the released acidity characterized by n ‐propylamine temperature‐programmed decomposition was correlated to the specific position of L rp . The results show that the acid density is roughly homogenous while the acid strength is heterogeneous within the crystal grains. From the outer surface to the center of the crystal grains, the strength of the Brønsted acid sites increase gradually.